2011
DOI: 10.2165/11586630-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Venlafaxine Extended Release 75 mg and Desvenlafaxine 50 mg in Healthy CYP2D6 Extensive and Poor Metabolizers

Abstract: In contrast to venlafaxine ER 75  mg, the pharmacokinetics of desvenlafaxine 50  mg is not significantly impacted by CYP2D6 genetic polymorphisms. PMs receiving venlafaxine ER 75  mg had significantly lower O-desmethylvenlafaxine and higher venlafaxine plasma concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 21 publications
1
46
0
Order By: Relevance
“…Phase I hepatic metabolism of desvenlafaxine appears to play a small role in its elimination, marked by metabolism to N,O-didesmethylvenlafaxine by the cytochrome P450 (CYP450) 3A4 pathway [5]. Because desvenlafaxine is primarily metabolized via glucuronidation, and clinical reports have shown that desvenlafaxine exerts minimal effects on the activities of the CYP450 enzymes or p-glycoprotein, the potential ability of other drugs to alter desvenlafaxine metabolism is low [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Phase I hepatic metabolism of desvenlafaxine appears to play a small role in its elimination, marked by metabolism to N,O-didesmethylvenlafaxine by the cytochrome P450 (CYP450) 3A4 pathway [5]. Because desvenlafaxine is primarily metabolized via glucuronidation, and clinical reports have shown that desvenlafaxine exerts minimal effects on the activities of the CYP450 enzymes or p-glycoprotein, the potential ability of other drugs to alter desvenlafaxine metabolism is low [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Desvenlafaxine is a selective serotonin and norepinephrine reuptake inhibitor. [1][2][3] Literature review reveals that methods have been reported for analysis of venlafaxine by UV spectrophotometry [4] and HPLC, [5,6] identification of desvenlafaxine, the major active metabolite of venlafaxine by HPLC; [7] stability-indicating HPLC for estimation of venlafaxine; [8,9] determination of venlafaxine and its three metabolites in human plasma by HPLC-MS=ESI; [10,11] chiral HPLC analysis of venlafaxine metabolites in rat liver; [12] and analysis of venlafaxine in tablet by HPTLC. [13] To our knowledge, there have been no published articles related to the stability indicating HPTLC for determination of desvenlafaxine in pharmaceutical dosage form.…”
Section: Introductionmentioning
confidence: 99%
“…These findings can be considered consistent with current knowledge of the mechanisms of action of these drugs. [36][37][38][39] Pertaining to sertraline, the high incidence of insomnia associated with this drug could be the consequence of its mechanism of action. In particular, bupropion is the only antidepressant that selectively inhibits the reuptake of dopamine and noradrenaline.…”
Section: Discussionmentioning
confidence: 99%